2016
DOI: 10.1007/s40616-016-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Hearing About Cancer Influence Stimulus Control? An Exploratory Study of Verbal Modulation of Stimulus Generalization

Abstract: Participants first became familiar with an image showing moderate symptoms of the skin cancer melanoma. In a generalization test, they indicated whether images showing more and less pronounced symptoms were Blike the original.^Some groups (cancer context) were told that the images depicted melanoma and that the disease is deadly unless detected early. Control groups were not told what the images depicted. For control groups, generalization gradients were fairly typical of what is normally reported in the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Covert stimulation may also influence an individual’s engagement in prevention-related behaviors. Critchfield and Reed ( 2016 ) suggested that people’s private psychological experience can actually interfere with such behaviors. These authors taught undergraduate participants to discriminate between melanoma and nonmelanoma images, and found that discriminations were disrupted when participants were given verbal information about the risks and mortality rates of skin cancer.…”
Section: Some Obstaclesmentioning
confidence: 99%
“…Covert stimulation may also influence an individual’s engagement in prevention-related behaviors. Critchfield and Reed ( 2016 ) suggested that people’s private psychological experience can actually interfere with such behaviors. These authors taught undergraduate participants to discriminate between melanoma and nonmelanoma images, and found that discriminations were disrupted when participants were given verbal information about the risks and mortality rates of skin cancer.…”
Section: Some Obstaclesmentioning
confidence: 99%
“…For example, experimental studies have analyzed how language effects health-related behaviors. These include an examination of the effects of verbal rules on patients’ breast self-examinations (Meyerowitz & Chaiken, 1987 ), and the identification of cancerous skin lesions as a function of verbal information about melanoma (Critchfield & Reed, 2016 ).…”
Section: Keys To the Kingdom: Scaling Upmentioning
confidence: 99%
“…tobacco marketing (Biglan et al, 2018), and affecting patients' self-examination behavior in health care settings (e.g., Critchfield & Reed, 2016;Meyerowitz & Chaiken, 1987).…”
Section: Final Thoughtsmentioning
confidence: 99%
“…By altering the value of such consequences, an augmental may thus indirectly increase or decrease behavior. Numerous experimental studies have analyzed the effects that rules, especially augmentals, have on dimensions of behavior, such as online consumer purchasing behavior (Fagerstrom et al, 2010), patients' breast self-examination (Meyerowitz & Chaiken, 1987), the identification of cancerous skin lesions (Critchfield & Reed, 2016), exercise intensity (Jackson et al, 2016), and large-scale marketing in media on tobacco consumption among youths (Biglan et al, 2018). Based on the findings from previous studies, it is not surprising that augmentals are frequently used in political speeches that aim to change public behavior involved in abstract and remote contingencies.…”
mentioning
confidence: 99%